2018
DOI: 10.1016/j.scr.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric muscle loss injury repair using in situ fibrin gel cast seeded with muscle-derived stem cells (MDSCs)

Abstract: Volumetric muscle defect, caused by trauma or combat injuries, is a major health concern leading to severe morbidity. It is characterized by partial or full thickness loss of muscle and its bio-scaffold, resulting in extensive fibrosis and scar formation. Therefore, the ideal therapeutic option is to use stem cells combined with bio-scaffolds to restore muscle. For this purpose, muscle-derived stem cells (MDSCs) are a great candidate due to their unique multi-lineage differentiation potential. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…140 Another study evaluated the efficacy of muscle-derived stem cells (MDSCs) combined with fibrin gel for VML repair in immunodeficient mice. 134 At 4 weeks post-injury, this combined approach showed that MDSCs differentiated into new myofibers and significantly increased muscle mass along with a significant decrease in fibrotic tissue deposition. The number of small fibers with centrally located nuclei were reported to increase with treatment indicating significant increase of regenerative fibers in the engrafted area of treated muscles (Fig.…”
Section: Satellite Cells and Myoblasts Transplantation With Biomaterialsmentioning
confidence: 91%
See 2 more Smart Citations
“…140 Another study evaluated the efficacy of muscle-derived stem cells (MDSCs) combined with fibrin gel for VML repair in immunodeficient mice. 134 At 4 weeks post-injury, this combined approach showed that MDSCs differentiated into new myofibers and significantly increased muscle mass along with a significant decrease in fibrotic tissue deposition. The number of small fibers with centrally located nuclei were reported to increase with treatment indicating significant increase of regenerative fibers in the engrafted area of treated muscles (Fig.…”
Section: Satellite Cells and Myoblasts Transplantation With Biomaterialsmentioning
confidence: 91%
“…Combining cells with candidate biomaterials may overcome issues associated with acellular scaffolds and cell‐only therapies. Such combination therapies have shown promising results in animal models and may provide a potential therapy in the near future . The following section describe some of the promising scaffold technology that has been developed in combination with cellular therapies over the recent years.…”
Section: Biomaterials For Skeletal Muscle Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Konigsberg long pointed out the importance of the extracellular matrix (ECM) protein collagen as a critical component to the development of muscle colonies, which led to its widespread use in SMTE . Since then, other natural and synthetic materials such as fibrin, alginate, polycaprolactone (PCL)‐based polymers, and various strategies have been developed to generate skeletal muscle tissues in vitro. Especially, the engineering of muscle fibers in vitro requires the culture of myoblasts in an anisotropic environment, promoting their alignment, favoring their fusion and the myogenesis .…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…To expose the tibialis anterior muscle, a longitudinal incision was made, followed by the creation of a wedge-shaped defect of 6 mm × 3 mm × 4 mm in length, width, and depth. For in situ casting of the MDSCs with fibrin gel, freshly harvested MDSCs (1 × 10 6 ) were re-suspended in 20 μl of fibrinogen solution (MedChemExpress) with or without 100 nM of SW033291, and the muscle defect was filled with the solution followed by addition of thrombin solution (5 IU/2 μl, MedChemExpress) to induce gel casting [42]. After 2 min waiting period to ensure gel solidification, the wound was carefully covered with the fascia and skin and secured using sutures.…”
Section: Surgical Procedures and Gel Castingmentioning
confidence: 99%